Efektivitas Pemahaman Standar Audit Terhadap Penyusunan Opini Laporan Audit Pada Kantor Akuntan Publik XY - Qanita Azzahra Widiatmoko; Arif Fajar Wibisono (Economic Reviews Journal, 2025)
Financial statement audits have an important role in ensuring that the financial statements that have been prepared by the company are in accordance with accounting standards, and applicabel regulations, as well as to maintain a balance between the interest of company management and other stakeholders. In order for ther audit process to run effectively and efficiently, auditors need to comply with the auditing standars set by the Indonesian Institute of Certified Public Accountants. The purpose of this study was to determine whether the XY Public Accounting Firm has adequate operational standards, and whether the auditors in the XY Public Accounting Firm understand and implement the operational audit standards set by IAPI. The research method used is descriptive qualitative method, and the research source is based on interviews with KAP XY auditors, research questionnaires containing audit standards 100-500, and documentation. Based on the data that the author has obtained, the results of the study indicate that the XY Public Accounting Firm has implemented the audit standards properly, but in its implementation there are still several challenges faced by KAP XY, one of which is the discovery of differences in understanding of audit standards between KAP XY auditors, indicating that there are several audit standards that have not been fully effective in their application in KAP XY.